PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH PROMOSI PADA PRODUK EIGER (Studi pada mahasiswa fakultas ekonomi dan bisnis Universitas trunojoyo madura) - Balyani, Ach; Suyono, Suyono (Eco-Entrepreneur, 2025)
This study aims to analyze the influence of brand image on purchasing decisions of Eiger products mediated by promotion, with the object being students of the Faculty of Economics and Business, Trunojoyo University, Madura. The background of this study is based on the importance of brand image in shaping consumer perceptions and the role of promotion in strengthening this influence on purchasing decisions. The method used is a quantitative approach by distributing questionnaires to respondents selected by purposive sampling. The results of the study indicate that brand image has a significant effect on purchasing decisions directly and indirectly through promotion. This finding indicates that companies need to pay attention to strong brand imaging and effective promotion in order to encourage consumers in making purchasing decisions. The implications of this study provide suggestions to Eiger management to continue to strengthen brand identity and design attractive promotional strategies that are in accordance with market needs, especially the student segment.